Kompetence kineziologa in njegova vloga v javnem zdravstvu v povezavi z zdravniki družinske medicine - Pustivšek, Suzana (Šport (Ljubljana), 2018)
Kinesiology is the science of body movement, researching the impact of it on health, physical capacity and quality of life. In the public health centre, the work of a kinesiologist is strongly depended of good cooperation with general practitioner (GP). They treat patients also in the period when the disease is not present yet, but risk factors are already significant. This is the moment when the preventive actions in cooperation with kinesiologist are needed, since physical inactivity is known to be a strong risk factor for several chronic disease for early death. Cooperation of GP with kinesiologist should be in two different aspects; primary and secondary prevention and post-rehabilitation. Some authors emphasize that a kinesiologist, is the only person who is primarily responsible and competent for counselling in the field of physical activity within the public health centre, although he is officially not defined as medical personal yet. Several positive effects of planned, structured and individualized physical activity support the fact that the presence of kinesiologist in public health is essential. Its work should be focused in both, prevention and post-rehabilitation area.
Keywords: kineziologija; medicina; rehabilitacija; sodelovanje; šport; zdravstvo